Business Licensing as An Effort to Improve Msme Businesses Recipient of Pekanbaru City Baznas AID - Afriyanti, Delima (Universitas Alma Ata, 2024)
Increasing business in micro, small, and medium enterprises (MSMEs) cannot be separated from sufficient funds sourced from bank and non-bank institutions. One of the social institutions that distributes funds is Baznas Pekanbaru City which distributes zakat funds to Pekanbaru City MSMEs through the Pekanbaru Prosperous program. This type of research is field research and the method used is qualitative with a phenomenological approach. The research results show that the number of MSMEs financed by Baznas is 198 MSMEs, however, the number of MSMEs that take part in business improvement educational activities is 100 MSMEs. The number of 100 MSMEs that do not yet have business permits is 68 MSMEs. Business licensing is considered difficult to administer and requires large costs. Together with STAI IMSYA Pekanbaru, Baznas Pekanbaru City synergizes in educational activities to improve the business and economy of Mustahik. The problems of MSMEs receiving Baznas Pekanbaru City assistance can be resolved with the distribution of zakat by BAZNAS Pekanbaru City and education on business improvement through business licensing by STAI IMSYA Pekanbaru which provides knowledge and control of MSME businesses so that MSMEs can keep up with developments in digitalization by using gadgets and accessing the business licensing system. free of charge which has been provided by the government, namely the Online Single Submission System (OSS) to improve their business, so that some mustahik can become muzakki.